Fabrication of an AMC/MMT Fluorescence Composite for its Detection of Cr(VI) in Water - Wei, Yanke; Mei, Lefu; Li, Rui; Liu, Meng; Lv, Guocheng; Weng, Jianle; Liao, Libing; Li, Zhaohui; Lu, Lin (Frontiers in Chemistry, 2018)
Hexavalent chromium species, Cr(VI), which can activate teratogenic processes, disturb DNA synthesis and induce mutagenic changes resulting in malignant tumors. The detection and quantification of Cr(VI) is very necessary. One of the rapid and simple methods for contaminant analysis is fluorescence detection using organic dye molecules. Its application is limited owing to concentration quenching due to aggregation of fluorescent molecules. In this study, we successfully intercalated 7-amino-4-methylcoumarin (AMC) into the interlayer space of montmorillonite (MMT), significantly inhibited fluorescence quenching. Due to enhanced fluorescence property, the composite was fabricated into a film with chitosan to detect Cr(VI) in water. Cr(VI) can be detected in aqueous solution by instruments excellent, ranging from 0.005 to 100 mM with a detection limit of 5 μM.